A Strong Argumentative Orientation Makes the Cognitive Closure Easier: The Case for a Persuasive Health Message - Vincent Coppola; Fabien Girandola; Odile Camus (Studia Psychologica, 2020)
The rationale of this study is that scalar adverbs are likely to act as a convenient means to achieve cognitive closure because they stress the argumentative orientation of the message. Based on this assumption, an experiment shows that the introduction of scalar adverbs in the message decreases the extent of its cognitive elaboration and increases its perceived quality and effectiveness for people high in need for closure, but not for people low in need for closure, for whom the outcomes are reversed with regard to perceived quality and persuasiveness of the message. To what extent such outcomes are likely to be affected by some variables traditionally studied in the persuasion literature is addressed in the discussion.